A technique of the sagittal split mandibular ramus osteotomy modified for the Japanese prognathism - WADA, Takeshi; IBUKI, Kaoru; KOGO, Mikihiko; NISHIO, Juntaro; YAKUSHIJI, Noboru; YOSHIDA, Kenmi; SAKUDA, Mamoru; GOTO, Tomonobu; TSUCHIYA, Masafumi; MIYAZAKI, Tadashi; MATSUYA, Tokuzo (Japanese Journal of Oral and Maxillofacial Surgery, 1985)
The sagittal split mandibular ramus osteotomy, established b Obwegeser in Europe, is recognized and utilized internationally as an useful procedure fo orthognathic surgery of mandibular prognathism. However, as indicated by the anthropologist, the skeletal architecture of Orientals including Japanese is not consistent with those of the Caucasions. The authors have modified the sagittal split mandibular ramus osteotomy so it can be applied for the maxillomandibular structures of Orientals. The present article demonstrates the newly modified surgical procedure with a report of 3 cases treated by this technique.